The effects of warming up strategies for sprint performance: Emerging approaches - Gil, Maria Helena Gonçalves (2019)
In recent years, the benefits of warm-up in sports performance have received a special interest. New methods have been included in warm-up procedure, but few are known about the effects on running performance and biomechanical responses. Thus, the purpose of the current thesis was to analyze the effect of recent trends of warm-up tasks on sprint performance. Specifically, to verify the effects of including ballistic exercises in warm-up procedures and to analyze the impact of changing biomechanical running patterns during warm-up, conducting a performance, biomechanical, physiological and psychophysiological evaluation of sprints. For this, the following steps were performed: (i) qualitative review on warm-up and performance, focusing on the emerging methods; (ii) to verify the acute effects of a warm-up including ballistic exercises inducing a post-activation potentiation, easy to apply on a real competition context, in repeated 100m running performance; (iii) to understand the acute physiological, psychophysiological and biomechanical responses of including ballistic exercises in repeated 30m running performance; (iv) to analyze the effect of manipulating running kinematics (stride length (SL) and stride frequency (SF)) during warm-up in repeated 30m running performance. The main conclusions of the study were: (i) considering the new trends that have emerged, it can be suggested positive effects on performance after short duration stretches followed by specific muscle activation exercises, and after dynamic stretching, both depending on the duration and intensity; short-duration maximal efforts and specific to the following activity, followed by few minutes of recovery, provide beneficial neuromuscular responses and improved performance in high-intensity and short-term efforts; passive heating during the transition phase between warm-up and main exercise lead to optimization of subsequent performance; (ii) there were benefitial effects of warm-up in 30m and 100m sprinting; (iii) the 100m race is equally optimized after warm-up with or without post-activation potentiation, but with different running kinematics (iv) the positive effects of warm-up on 30m running was caused by faster initial 15m and increased SL in the last 15m of the trial; v) no additional effects on 30m were found after including ballistic exercises during warm-up; (vi) a warm-up focusing in higher SL or higher SF did not result in different 30m sprint performances and running kinematics, despite different running strategies occurred (faster initial meters after warm-ups stimulating SF and faster final meters after warm-up stimulating SL); (vii) the results highlighted the individual response to each warm-up procedure. The main findings of this work emphasize the importance of the warm-up design for short running distances and the need of individualization for optimized performances. Further studies are needed to deeply understand their effects on performance.